Endocrine Diseases as a Cause of Short Stature in Children - Aditiawati Aditiawati (Arkus, 2016)
Growth abnormalities of short stature or tall stature are closely related to body disproportion. Humans experience changes in body proportions from infancy to adulthood. This is due to changes in organs and organ systems at each stage of an individual's life. Differences in growth rates in body organs affect differences in body proportions at each stage of an individual's life. This is related to osseous maturation, which is influenced by the endocrine system. There is a change in the ratio of the lower and upper segments according to age and arm span. The combination of low body weight with short stature or a lighter weight-to-height ratio indicates a chronic systemic disorder as a cause of short stature. A combination of short stature and being overweight or an increased ratio of body weight to height are essential clues to the possibility of an endocrine disorder as a cause of short stature.